Debt Management Reform Plan : Madagascar - World Bank (Washington, DC, 2014)
The reform plan pillars outlined in this report build on the findings of the 2013 World Bank Debt Management Performance Assessment (DeMPA) for Madagascar and the discussions held during this mission with the central government representatives. Recent presidential elections and envisaged inauguration of the new government provides an enabling environment for engaging into broad economic and institutional reforms. Improvement of the governance practices and continuation of the public finance management reforms are among priorities stipulated in the President's reform agenda. It is important to mention that during the last two years MoFB's Treasury undertook a number of initiatives to improve government debt management. The Public Debt Directorate (DDP) was reorganized in 2012 and additional staff was hired during the last calendar year. Improvement of existing legal framework was initiated by the DDP in close cooperation with legal advisers of the Treasury. The main areas of reforms identified include: (i) improvement of the legal framework, (ii) formulation of a debt management strategy, (iii) improvement of central government borrowing policies, and (iv) operational risk management.